2012
DOI: 10.12765/cpos-2011-15
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere Better Than Here?<br>The Subjective Well-Being of German Emigrants and Remigrants<br>

Abstract: The paper investigates in the question if and how the subjective well-being (SWB) of German emigrants, German non-migrants, and German remigrants differ. Based on regression analyses of data from the European Social Survey (ESS) the analyses focus on life satisfaction and happiness as main indicators of SWB. It turns out that German emigrants show increased SWB compared to German non-migrants or remigrants. However, these findings cannot be explained by differences in the socio-economic or socio-demographic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
20
0
3
Order By: Relevance
“…However, empirical tests to link the life satisfaction of immigrants to that which is typical in their country of origin are rarely provided in the literature; this article fills this gap. It adds to the findings of Erlinghagen (2011), who showed that, after controlling for basic predictors, there is little or no difference in the life satisfaction levels displayed by stayers in Germany and German migrants to selected European countries. Bartram (2013b) reported similar results for Romanians.…”
Section: Cultures Of Life Satisfaction and Their Consequencesmentioning
confidence: 64%
“…However, empirical tests to link the life satisfaction of immigrants to that which is typical in their country of origin are rarely provided in the literature; this article fills this gap. It adds to the findings of Erlinghagen (2011), who showed that, after controlling for basic predictors, there is little or no difference in the life satisfaction levels displayed by stayers in Germany and German migrants to selected European countries. Bartram (2013b) reported similar results for Romanians.…”
Section: Cultures Of Life Satisfaction and Their Consequencesmentioning
confidence: 64%
“…A previous report performed in Spain concluded that immigrants who resided in Spain for less than 10 years showed a better state of mental health than the Spanish population [54]. Other works outside Spain have also reported that the mental health of immigrants was found to be similar or better than that of the native population of the destination country [55][56][57]. However, it is important to point out that data obtained about a good mental health state among immigrants may be biased, since people with poorer mental health would have lower possibilities to migrate.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps immigrants in our sample compared their achievements later in life with those of friends and relatives from their home country, and this strategy contributed to increase their levels of satisfaction. There is evidence that immigrants tend to have higher levels of life satisfaction than stayers from their home countries (Erlinghagen, 2011). Alternatively, the high levels of life satisfaction of older Hispanics might stem from comparisons with themselves at the beginning of their migratory careers.…”
Section: Discussionmentioning
confidence: 99%